Combating striga in Africa - Kim, S.K. (1991)
Information on current progress in the refinement of screening techniques identification of resistant germplasm and breeding lines and assessment of crop losses due to striga attack is presented. A new laboratory-cum-pot steel mesh roll technique which permits interaction of stimulants with soil was developed and found effective in differentiating low from high stimulant-producing sorghum lines. Results correlated well with those from field screening of breeding lines for striga resistance.